Hubungan Proteinuria Dengan Jumlah Trombosit pada Pasien Infeksi Dengue - Charisma, Acivrida Mega; Farida, Elis Anita; Anwari, Farida (Jurnal Analis Kesehatan, 2022)
Dengue Hemorrhagic Fever is a viral infectious disease that often causes high morbidity and mortality in Indonesia every year. Platelet count is one of the parameters that can be used as an indication in the diagnosis of this disease. In its development, severe dengue infection often causes proteinuria because there are no abnormalities in plasma, this condition will continue as the severity of the disease increases. This study aims to find out whether there is a relationship between thrombocytopenia and the incidence of proteinuria in dengue infection. This type of research is a retrospective analytic with a cross-sectional design, the data were taken from medical records at the Vita Medika Clinic laboratory in March – June 2020, including data on examination of thrombosis and examination of proteinuria in dengue patients. Data were analyzed by Spearman correlation test. The results of the study showed that there was a relationship between the number of platelets and the incidence of proteinuria in dengue infection with a value of p=0.002 (p<0.05). This is indicated by the mean, median, maximum and minimal platelet counts in respondents with proteinuria which were lower than respondents without proteinuria.